PENGELOLAAN KAWASAN KONSERVASI TAMAN HUTAN RAYA SULTAN SYARIF HASYIM DI KECAMATAN MINAS KABUPATEN SIAK PROVINSI RIAU - Novita, Retno; Yuliani, Febri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The research is investigate to describe the managing of conservation great forest garden of Sultan Syarif Hasyim region of Minas Subdistrict Siak Regency Riau Province. The region of conservation is perpetuation of nature region with the purpose are to plant collection and the nature fauna or made in, original kinds or not, that useful for research needs, knowledge, education, cultivation support, culture, tourism and recreation. Based on field observation and the data the problems is conservation region of great forest garden not managing well with sign open new land by specific person that they used for plant coconut because less the managing and handling land in that region. The purpose of this research is to know the managing of conservation great forest garden of Sultan Syarif Hasyim region of Minas Subdistrict Siak Regency Riau Province.The concept of theory that used is Managemen Function (Managing) start from planning, organization, implementation and managing. This research used qualitative research method with investigate the data with describtive way. In collecting the data the researcher used interview technique, observation and documentation.The result of this research is produce the conclusion results that the managing did by UPT KPHP Model Minas Tahura in enviroment live’s official and forestry Riau Province is still in category not optimum. There were some not optimum in planning, organization, implementation and managing. Then, there were some factor that influence the steps of UPT KPHP Model Minas Tahura in managing conservation great forest garden region was the source power of human that still less for checking the region, calculation operational mecanism that should complete and also the support of government and miter work that needs.Keywords: Management, Conservation, Great Forest Garden